Capacitance Temperature Dependence Analysis of GaN-on-Si Power Transistors - Florian Rigaud-Minet; Julien Buckley; William Vandendaele; Matthew Charles; Marie-Anne Jaud; Elise Rémont; Hervé Morel; Dominique Planson; Romain Gwoziecki; Charlotte Gillot; Véronique Sousa (Energies, 2022)
Many kinds of defects are present in the different layers of GaN-on-Si epitaxy. Their study is very important, especially because they play a significant role on the device characteristics. This paper investigates the cause of the temperature dependence of the output and Miller capacitance at three temperatures: 25 °C, 75 °C and 150 °C of GaN-on-Si power transistors. In particular, this study focuses on the temperature dependence of the depletion voltage seen in these characteristics due to the progressive depletion of the two-dimensional electron gas (2DEG) under the device field plates. First, variations of the epitaxial growth are studied, showing that the intrinsic carbon concentration does not play a significant role. Secondly, the deep acceptor trap origin of the temperature dependence is analyzed with a TCAD simulation study. Thirdly, by adjusting TCAD parameters and binding them with experimental concentrations to fit experimental data, trap properties were obtained. The comparison of these properties with the acceptor traps in the literature suggests that the origin is a gallium vacancy tied to oxygen atom(s) on the N site.